Pengaruh Interaksi Corporate Social Responsibility dan likuiditas Saham Terhadap Earnings Response Coeficient Studi pada Perusahaan Pertambangan di Bursa Efek Indonesia - Maria Yosaphat Dedi Haryanto (JEMAP, 2018)
This study aims to prove that interaction between CSR and stock’s liquidity will affect earnings response coeficient. Earnings response coefficient is a measure of the magnitude of market reaction to information about the company as reflected by the release of financial statements, especially profit information. So it can be said ERC can reflect the quality of profit information. Reputation of a company becomes a factor that supports the quality of profit information. Corporated social responsibility is a form of corporate concern to the environment that can show the added value of the company in the eyes of investors. Meanwhile, stock liquidity is the amount of stock trading volume in the stock exchange that can give an idea of how big the market or investors have interest in these shares. This study uses a sample of mining companies listed on the Indonesia Stock Exchange and data analysis using Moderated Regression Analysis (MRA). The result of the research proves that alternative hypothesis is accepted. So it can be concluded that the interaction of corporated social responsibility with stock trading liquidity affects the quality of earnings information.